About use of adaptive semantic models in ecological education - T. Sh. Shihnabieva; N. M. Bulaeva; N. O. Guseinova (Юг России: экология, развитие)
The information systems used in formation(education) now, are not focused on model of the concrete user and are not adaptive. Process of training with use of information and communication technologies in our work is considered as information semantic system in which basis of functioning one of intellectual models of representation of knowledge as a semantic network lays. Used by us in educational process adaptive semantic models allow to distinguish a level of preparation of trainees and promote the profound studying of a subject domain.